Safety and Efficacy of Subcutaneous Pasireotide in Patients With Cushing's Disease: Results From an Open-Label, Multicenter, Single-Arm, Multinational, Expanded-Access Study - Fleseriu, Maria; Iweha, Chioma; Salgado, Luiz; Mazzuco, Tania Longo; Campigotto, Federico; Maamari, Ricardo; Limumpornpetch, Padiporn (Frontiers in Endocrinology, 2019)
Introduction: The efficacy and safety of subcutaneous (sc) pasireotide have been evaluated in a Phase III trial. Here, we report safety and efficacy results from a multinational, expanded-access study of pasireotide sc in patients with Cushing’s disease (CD) in a real-world setting (clinicaltrials.gov identifier: NCT01582061). Methods: Adults with active CD previously untreated with pasireotide were enrolled; pasireotide sc was initiated at 600µg twice daily (bid; EU countries) or 900µg bid (non-EU countries; 600µg bid in patients with impaired glucose metabolism). Pasireotide dose could be adjusted in 300µg increments/decrements to a maximum of 900µg bid or minimum of 300µg bid for sustained urinary free cortisol (UFC) normalization/tolerability issues. Primary objective: document the safety of pasireotide sc in patients with CD. Key secondary objectives: assess the proportion of patients with mean UFC (mUFC) not exceeding the upper limit of normal (ULN) and changes from baseline in clinical signs/symptoms and quality of life (QoL) to weeks 12, 24 and 48. Results: One hundred and four patients received pasireotide: female, n=84 (80.8%); median duration of pasireotide exposure, 25.1 weeks; median (range) baseline mUFC, 321.2nmol/24h (142–10,920; 2.3 × ULN [1.0–79.2]). Forty (38.5%) patients completed the study. The most common reasons for premature discontinuation of pasireotide were unsatisfactory therapeutic effect (n=26, 25.0%) and adverse events (AEs; n=20, 19.2%). Drug-related grade 3/4 AEs or drug-related serious AEs (primary endpoint) were documented in 42 (40.4%) patients, most commonly diabetes mellitus (n=12, 11.5%) and hyperglycemia (n=8, 7.7%). All patients experienced ≥1 AE and most (n=102; 98%) reported ≥1 drug-related AE; six (5.8%) patients discontinued treatment because of hyperglycemia-related AEs. At weeks 12, 24 and 48, respectively, 36/66 (54.5%), 22/46 (47.8%) and 9/21 (42.9%) evaluable patients had normalized mUFC levels. Clinical signs/symptoms and QoL were also improved. Conclusions: In an international, real-world, clinical-practice setting, pasireotide sc was generally well tolerated (no new safety signals were identified), effectively reduced UFC (normalization in 50% of evaluable patients) and improved clinical signs and QoL in patients with CD. While hyperglycemia-related AEs were common, consistent with previous studies, most were manageable, with <6% of patients discontinuing treatment because of these events.